Tough choices : bearing an illegitimate child in contemporary Japan - Hertog, Ekaterina, 1979- (Stanford University Press, 2009)
This book offers the first detailed study of why the number of unmarried Japanese mothers has hardly changed since 1955, despite the prevalence of certain factors in Japan (more later marriages, higher divorce rate, and so on) that have brought about sign.